THE EFFECT OF JUMPING FROG MEDIA WITH MANIPULATIVE MOVEMENT ON SUBTRACT MATERIAL ON LEARNING OUTCOMES OF GRADE I STUDENTS AT STATE ELEMENTARY SCHOOL 94 PALEMBANG: Pengaruh Media Katak Melompat Dengan Gerak Manipulatif Materi Pengurangan Terhadap Hasil Belajar Siswa Kelas I SD Negeri 94 Palembang - Eka Wahyuningsih; Muhsana El Cintami Lanos; Daryono (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This study amis to determine the effect of jumping frog media with manipulative movement on subtraction material one the learning outcomes of grade I students at state elementary school 94 Palembang. This is due to a lock of engaging media due to the continued dominance of convensional methods such as lectures, textbooks, and whiterboards. This situation has resulted in low student mathematics learning outcomes. To address this, learning media are needed that can help students learning through real-life and enjoyable activities, such as the jumping frog model wit manipulative movements, so that students can more easily understand the concept of subtraction through direst experience. The method used in this study was a Pre -Exsperimental Design. Data on student learning activities were collected through tests and documentation. Data on  student learning outcomes were collected using essay  questions. The one group pretest dan posttest design method was all 34 grade I students, and the sampel used was quentitative analysis. The results of the hypothesis test or t-tes yielded a significance level of 0,000<a ( a=0,025), therefore ho was rejected and Ha was accepted. Therefore, it can be concluded that the jumping frog media with manipulative movements in the subtraction material has an effect on the learning outcomes of first-grade students at SD Negeri 94 Palembang